SPATIAL AND TEMPORAL ASPECTS OF BENTHIC THANATOCOENOSES IN A MEDITERRANEAN INFRALITTORAL CAVE (Rivista italiana di Paleontologia e Stratigrafia, 1997)
Sedimentology,faunistic and radiometric analyses were performed on three bottom cores from the Accademia Cave (Ustica,Southern Tyrrhenian Sea). The two outermost sites (near the cave openings) contain coarses sediments,while the innermost sample (from a sheltered area) consists of noticeably finer sediments.Similarly,differences are present in the benthic thanatocoenoses at these sites. The innermost core is more homogeneous,essentially authochthonous and dominated by "cave species"while the cores near the entrance of the cave are more heterogeneous and contaminated by external bioclasts. These difference indicate a confinement gradient mainly affected by hydrodynamics. Conversely,radiometric data indicate few signs of temporal variations,at least for the last 1,000 years recorded in the sediments studied. A slight topward confinement increase in the innermost core may be related to local changes in cave topography.